Metatranscriptomic approach to characterize microbiome and identify molecular markers for early detection of “Hoja de malvón” disease in Vitis vinifera cv. Malbec - Paolinelli, Marcos; Escoriaza, Maria Georgina; Cesari, Cecilia Alicia; Hernández-Martínez, R.; Gomez Talquenca, Gonzalo; Garcia Lampasona, Sandra Claudia (International Council on Grapevine Trunk Diseases (ICGTD), 2025)
Poster